2021
DOI: 10.1590/1806-93042021000400006
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in adolescence in Brazil: associated factors with maternal age

Abstract: Objectives: describing maternal characteristics, risk behavior, obstetric data, prenatal care and childbirth in adolescent mothers in Brazil (age groups: 12-16 years and 17-19 years). Methods: hospital-based cross-sectional study substantiated by Nascer no Brasil”, (Born in Brazil) data. The study encompassed puerperal adolescent mothers from all regions in the country, and their newborns. Chi-square test was used to compare adolescents in the 12-16 years old age group and those in the 17-19 years old age gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
2
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 21 publications
2
4
2
7
Order By: Relevance
“…The primiparity index in the sample was 34.7% and 81.8% among adolescents, results similar to those of the Nascer no Brasil study (25)(26)(27) . It is noted that an association was found between primiparity and higher adherence to puerperal return visits.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The primiparity index in the sample was 34.7% and 81.8% among adolescents, results similar to those of the Nascer no Brasil study (25)(26)(27) . It is noted that an association was found between primiparity and higher adherence to puerperal return visits.…”
Section: Discussionsupporting
confidence: 88%
“…The study indicated low educational level among pregnant adolescents, similarly to data found in the Nascer no Brasil survey (25,27) . A qualitative study pointed out that 75% of adolescents interrupt schooling due to an ongoing pregnancy (28) .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…El estudio mostró baja escolaridad entre las adolescentes embarazadas, similar a los datos reportados en el estudio Nacer en Brasil (25,27) . Un estudio cualitativo mostró que el 75% de las adolescentes interrumpen sus estudios debido al embarazo (28) .…”
Section: Discussionunclassified